2019
DOI: 10.1186/s13045-019-0708-7
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: miR-195-5p/NOTCH2-mediated EMT modulates IL-4 secretion in colorectal cancer to affect M2-like TAM polarization

Abstract: Background: Tumor microenvironment (TME) is a complex environment containing tumor cells, tumor-associated macrophages (TAMs), interstitial cells, and non-cellular components. Epithelial-mesenchymal transition (EMT), as a major actor in cancer tumorigenicity and metastasis, was involved in the interaction between TAMs and tumor cells. However, the potential mechanisms of EMT and how EMT-programmed tumor cells affect M2-like TAMs still need further exploration. Methods: An integrated analysis of nine CRC miRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
135
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 171 publications
(153 citation statements)
references
References 45 publications
(58 reference statements)
9
135
0
Order By: Relevance
“…Moreover, Bergenfelz et al observed that Wnt5a was mainly located in CD163 + TAMs in breast cancer and could induce a tolerogenic phenotype of macrophages (24). Based on the above studies and our previous results (8,9), we speculated that Wnt5a might induce M2 polarization of TAMs to promote tumor development in CRC.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…Moreover, Bergenfelz et al observed that Wnt5a was mainly located in CD163 + TAMs in breast cancer and could induce a tolerogenic phenotype of macrophages (24). Based on the above studies and our previous results (8,9), we speculated that Wnt5a might induce M2 polarization of TAMs to promote tumor development in CRC.…”
supporting
confidence: 53%
“…Circulating tumor cells (CTCs) were captured, isolated, and identified by a novel CTCBIOPSY method as reported by our previous study (8,9,26). Briefly, 1 ml of blood of mice was first diluted with 4 ml of 0.9% physiological saline and then totally transferred to ISET tubes with an 8-µm diameter aperture membrane.…”
Section: Ctc Enrichmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Only original experimental studies to screen miRNAs that were differentially expressed (DE) between CRC and ANT in at least 40 human samples were included. Selection criteria, probe annotation, and data normalization were the same as described in previous reports (Sun et al, 2017a,b;Lin et al, 2019).…”
Section: Data Collection Preprocessing and Normalizationmentioning
confidence: 99%
“…A single model incorporating multiple biomarkers demonstrates improved performance and stability of prognostic value (Agesen et al, 2012;Marisa et al, 2013). However, further validation is still needed for the implementation of these miRNAs in standard CRC clinical practice, and the underlying mechanism remains to be elucidated (Huang et al, 2017;Lin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%